LAYING HEN HEALTH MANAGEMENT FOR INCREASING PRODUCTIVITY AND WELFARE OF FARMERS IN TOMBULUAN VILLAGE, TOMBULU DISTRICT, MINAHASA REGENCY - Palandeng, Indrie Debbie; Tielung, Maria V.J.; Wangke, Shinta.J.C.; Jan, Arrazi Hasan (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Laying hens are one of the types of chickens that have the potential to be raised and used as a source of income. Eggs are often used as breakfast menus, the basic ingredient for both wet cakes, pastries, bread, pudding or other snacks for all people because of their high nutritional content or adding a delicious and savory taste to processed foods. The high consumer demand for eggs makes the laying hen farming business the choice of the community to become a source of income. This phenomenon also occurred in Tombuluan Village, Community District, in Tombuluan Village, Tombulu District, Minahasa Regency. The business opportunity for laying hen farmers is very high, this is because egg consumption increases every year along with the increase in population, in addition, this business also has a more stable income with broiler farming because the productive period of laying hens can reach 2 years of production, enough time is used to generate profits for farmers. This also makes the chicken egg farmer business can be used as a promising business opportunity for the community in Toumbuluan Village. However, based on the initial survey, the proposer team found that the Laying Hen Farmers Group in Tombuluan Village did not understand the theories and business management well, especially including business development by producing higher quality products, financial and stock management, lack of asset management or marketing strategies that were still conventional. For this reason, this PKM business management is important to be implemented in order to provide knowledge and guidance to the farming community in Tombuluan Village who will be used as partners in this PKM activity. This PKM activity is expected to provide knowledge and abilities for laying hen farmers in implementing or managing their businesses. The technical implementation of this PKM activity includes providing assistance and business management training to chicken farmers and the TIM will follow up to see the implementation of partners. The output targeted by the PKM Team is the publication of accredited national journals.